Hydroborative reduction of amides to amines mediated by La(CH2C6H4NMe2-o)3. (14th December 2021) - Zhang, Fangcao; Guo, Chenjun; Gong, Mingliang; Xie, Hongzhen; Luo, Yunjie
Abstract : La(CH2 C6 H4 NMe2 - o )3 /HBpin is an efficient catalytic system for the deoxygenative reduction of primary, secondary and tertiary amides to amines. Abstract : The deoxygenative reduction of amides to amines is a great challenge for resonance-stabilized carboxamide moieties, although this synthetic strategy is an attractive approach to access the corresponding amines. La(CH2 C6 H4 NMe2 - o )3, a simple and easily accessible lanthanide complex, was found to be highly efficient not only for secondary and tertiary amide reduction, but also for the most challenging primary reduction with pinacolborane. This protocol exhibited good tolerance for many functional groups and heteroatoms, and could be applied to gram-scale synthesis. The active species in this catalytic cycle was likely a lanthanide hydride.